2016
DOI: 10.14687/jhs.v13i2.3778
|View full text |Cite
|
Sign up to set email alerts
|

Examining of leisure time participation, psychological well-being and leisure negotiation of university students<p>Serbest zaman katılımı, psikolojik iyi olma ve serbest zaman engelleri ile baş etme stratejilerinin üniversite öğrencileri üzerinde incelenmesi

Abstract: The aim of this study is to determine whether psychological well-being statuses of university students according to their genders, their leisure negotiation strategies and their leisure exercise participation have been differentiated or not and detect the relationship between psychological well-being, leisure negotiation strategies and leisure activities participation of students. Sample of the study consisted of 400 female and 400 male making 800 students at total. As data collection tool in the study was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 11 publications
0
2
0
6
Order By: Relevance
“…Although there are studies investigating the significant effect of gender on the psychological well-being (Roothman, Kirsten, & Wissing, 2003;Akhter, 2015) of university students (Chraif & Dumitru, 2015;Geçgin & Sahranç, 2017;Karabeyeser, 2013;Karaca & Yerlisu Lapa, 2016;Ulu, 2018), studies concluding that it significantly affects psychological well-being of pre-service teachers (Kumcağız & Gündüz, 2016) are relatively few in number. Although it is emphasized in the literature that the significance is in favor of females, it is concluded that male pre-service pre-school teachers feel psychologically much better than female pre-service pre-school teachers.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are studies investigating the significant effect of gender on the psychological well-being (Roothman, Kirsten, & Wissing, 2003;Akhter, 2015) of university students (Chraif & Dumitru, 2015;Geçgin & Sahranç, 2017;Karabeyeser, 2013;Karaca & Yerlisu Lapa, 2016;Ulu, 2018), studies concluding that it significantly affects psychological well-being of pre-service teachers (Kumcağız & Gündüz, 2016) are relatively few in number. Although it is emphasized in the literature that the significance is in favor of females, it is concluded that male pre-service pre-school teachers feel psychologically much better than female pre-service pre-school teachers.…”
Section: Discussionmentioning
confidence: 99%
“…Kadın öğrencilerin boş zaman spor aktivitelerinde yaşayacakları deneyimlerin sosyal yönünün ağır bastığı ve tercihlerini etkilediği görülmüştür. Diğer taraftan yapılan bir diğer araştırmada cinsiyete göre boş zaman engelleriyle baş etme stratejilerinde anlamlı bir farklılık görülmemesine rağmen boş zaman aktivitelerine katılım noktasında erkek öğrencilerin kadın öğrencilere göre daha fazla katılım gösterdikleri belirlenmiştir (Karaca, 2015).…”
Section: Tartişma Ve Sonuçunclassified
“…When the studies about life satisfaction were examined; Gökçe (2008) concluded that leisure activities had no effect on life satisfaction of individuals and, Karaman (2015) and Gezer (2014) concluded that life satisfaction is high among individuals who do sports for recreational purposes. Based on demographic characteristics, life satisfaction levels differ; Şahin (2010) and Keser (2005) concluded that gender variable has no effect on life satisfaction in their studies, while Öztürk (2014Öztürk ( ), Baştemur (2006, Taş (2011), Karaca and Lapa (2015) concluded that gender has significant differences in life satisfaction in their studies.…”
Section: Related Researchesmentioning
confidence: 99%